2014
DOI: 10.1007/s10695-014-9959-y
|View full text |Cite
|
Sign up to set email alerts
|

Stocking density and Piscirickettsia salmonis infection effect on Patagonian blennie (Eleginops maclovinus, Cuvier 1830) skeletal muscle intermediate metabolism

Abstract: The need to expand aquaculture production has led to other fish to be considered as potential species for culture, such as the sub-Antarctic notothenioid Eleginops maclovinus (Valenciennes, 1830). The aim of this study was to determine the cumulative effect of density and pathogen infection by protein extract of Piscirickettsia salmonis on skeletal muscle metabolism. In a first experiment, specimens were submitted to three different stocking densities: (1) 3.1 kg m(-3), (2) 15 kg m(-3) and (3) 60 kg m(-3), for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For instance, in E. maclovinus acclimated to different environmental salinities, G6PDH in the liver did not show variation, whereas in individuals of the same species exposed to high salinity conditions, activity of G6PDH decreased (Vargas‐Chacoff, Moneva, et al, ; Vargas‐Chacoff et al, ). Additionally, an increase in the hepatic activity of G6PDH has been observed in E. maclovinus exposed to stressful high stocking density conditions (Vargas‐Chacoff, Ortiz, et al, ). Their results, combined with our study, suggest that an increase of G6PDH after inoculation with AUSTRAL‐005 could be related to the need of glucose oxidation via pentose phosphate shunt, elevating the reducing power (NADPH) and lipid biosynthesis, which is needed as a source of energy due to a higher demand trigger by the antibiotic‐resistant strain.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…For instance, in E. maclovinus acclimated to different environmental salinities, G6PDH in the liver did not show variation, whereas in individuals of the same species exposed to high salinity conditions, activity of G6PDH decreased (Vargas‐Chacoff, Moneva, et al, ; Vargas‐Chacoff et al, ). Additionally, an increase in the hepatic activity of G6PDH has been observed in E. maclovinus exposed to stressful high stocking density conditions (Vargas‐Chacoff, Ortiz, et al, ). Their results, combined with our study, suggest that an increase of G6PDH after inoculation with AUSTRAL‐005 could be related to the need of glucose oxidation via pentose phosphate shunt, elevating the reducing power (NADPH) and lipid biosynthesis, which is needed as a source of energy due to a higher demand trigger by the antibiotic‐resistant strain.…”
Section: Discussionmentioning
confidence: 97%
“…Our results showed that after inoculation with both strains of P. salmonis , an increase in the cortisol levels was observed, being higher in fish injected with AUSTRAL‐005 (Figure a). This glucocorticoid is utilized as an indicator of stress in fish and can suppress the phagocytic and complement activity, increasing the susceptibility to develop the infection in the fish after P. salmonis inoculation (Pickering & Stewart, ; Vargas‐Chacoff, Martinez, et al, ; Vargas‐Chacoff, Ortiz, et al, ; Wendelaar‐Bonga, ). Previous studies have shown similar increases in E. maclovinus cortisol levels after being inoculated with total protein of wild‐type P. salmonis and then exposed to high stocking density (Vargas‐Chacoff, Martinez, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations